Determinants of International Migration: An Applied Study on Selected Arab Countries (1995-2017) - Morghem, Laila Touhami; Spetan, Khawlah Ali Abdalla (International Journal of Economics and Financial Issues, 2020)
The objective of this study is to analyze the pull and push factors as determination of international migration from selected Arab countries (Algeria, Egypt, Iraq, Jordan, Lebanon, Libya, Mauritania, Morocco, Sudan, Syria, Tunisia, Yemen) to western countries (Canada, France, Germany, Britain, USA), using Unbalanced Panel Data For the period of (1995-2017). The study aimed at developing an extended gravity model to investigate economic and non-economic determinants of international immigration using negative binomial regression; this is considered as the most appropriate to estimate the relationship between the number of immigrants as a dependent variable and other explanatory variables in this study. The dependent variable is an example of a count data, which takes positive integers numbers. After examining the hypotheses of the study, the results showed that the economic factor represented by per capita income in the receiving country is the strongest attraction for migrants from Arab countries. In aWddition to the presence of former immigrants from the same immigrant country in the receiving State, the study also found an increase in the number of immigrants from Arab countries since 2011. In contrast, distance between countries and poverty in the Arab countries are the main obstacles to international migration. Keywords: International Migration, Arab Countries, Negative Binomial, Gravity Model JEL Classification: J61 DOI: https://doi.org/10.32479/ijefi.9106